Match and Mismatch between Pre-Primary Teachers ' Beliefs and Classroom Instruction in Teaching and Learning to Read Kiswahili in Tanzania: Implications for Teacher Education - Shukia, Richard (Papers in Education and Development, 2018)
Teachers ' beliefs have the potential of influencing teachers ' instructional decisions and/or even accept, resist or renegotiate the mandated curriculum intentions. Yet, knowledge about these relations in Tanzania ' s pre-primary education is largely lacking. This study sought to narrow this gap of knowledge by exploring pre-primary teachers ' beliefs about learning and teaching to read Kiswahili in Tanzania, and the extent to which these beliefs are related to classroom instructional practices and curriculum intentions. The study was informed by a qualitative hermeneutic-phenomenology methodology. Twenty-one pre-primary teachers were involved in this study. Of these, three were males and 18 were females. Of the participants, six had primary teacher education background whereas two had attended a one-year pre-school training course. Empirical materials were generated over a period of six months using 21 semi-structured interviews, 12 classroom observations, 12 post-observation video-stimulated interviews, and content analysis of lesson plans and curriculum. The study findings reveal that teachers ' beliefs about teaching to read Kiswahili revolve around direct and systematic phonics instruction and integration of reading and writing activities. The findings further demonstrate that there was both match and mismatch between the teachers ' beliefs, their instructional practices and curriculum intentions. Thus, the study recommends the provision of on-going reflective teacher in-service training, fostering of teacher effective participation in curriculum development process, and doubling of efforts aimed to address contextual factors, which interrupt classroom instructional practices and affect the relationship between teachers ' beliefs and curriculum intentions. Keywords: Teachers ' beliefs, learning to read difficulties, pre-primary teachers